Propuesta de un manual de procedimientos para mejorar la Gestión del Talento Humano en la empresa Medihospital de la Ciudad de Loja, periodo 2019-2020 - Aguirre Torres, Carmen Alexandra (2020)
The objective of this research work is to prepare a proposal for a manual of procedures to improve Human Talent Management in the company Medihospital de la Ciudad de Loja, in order to contribute to an effective development of Human Talent Management. During the research work, it was necessary to carry out a diagnosis to know the current situation of the company in terms of Human Talent Management, for which the synthetic, descriptive, deductive and inductive methods were used, as well as information obtained thanks to the survey, the same one that was directed to the workers of the different areas, the interview with the general manager Ing. Ixania Azanza and the bibliographic review based on books, scientific articles and magazines; Regarding the results of the diagnosis, it was found that a job analysis, personnel planning, job evaluation is not carried out, recruitment is external, in the selection process the interview is used with greater preference and the committee in charge of carrying it out is made up of medical personnel, for induction they do not have a welcome manual, training is mandatory for workers, performance evaluation is developed by an external company, there are no promotions and there is no commitment from workers, therefore the management carried out is presented in an empirical and superficial way. The procedures manual contains: manual objectives, policies, scope, managers, concepts and procedures, which are described by means of process files and flow charts, such as job analysis, personnel planning, internal and external recruitment, selection, hiring, induction, performance evaluation, training, promotions, retirements, job evaluation, payment of salaries, dismissal of personnel due to disciplinary offenses, voluntary dismissal, vacations, leave and hygiene, occupational safety and occupational hazards, the document format is also attached that must be prepared according to each procedure to demonstrate its 5 execution and the correct formation of the selection committee with the general manager, head of human talent, immediate head of the vacant position and a professional in medicine is proposed.